SAP Integration Boosts Financial Transparency in Indonesia: Integrasi SAP Meningkatkan Transparansi Keuangan di Indonesia - Alkifa Wahyuning Tyas; Fityan Izza Noor Abidin (Universitas Muhammadiyah Sidoarjo, 2024)
This study evaluates the implementation of the SAP system at PT. Kimia Farma Pharmacy Sidoarjo Business Unit and its impact on financial report transparency. Using a descriptive qualitative method involving interviews, observation, and documentation, the research found that only four of nine SAP modules are used, yet the system is well-implemented. The SAP system enhances financial report transparency by meeting key transparency characteristics, thereby reducing fraud and ensuring accurate financial disclosures. This suggests that even partial SAP implementation can significantly improve financial transparency. Highlight: Limited Modules: Four of nine SAP modules are effectively utilized. Transparency Boost: SAP system enhances financial report transparency significantly. Fraud Reduction: Improved transparency reduces fraud and ensures accurate financial disclosures. Keyword: SAP system, financial transparency, qualitative analysis, Kimia Farma, financial reporting